Growing Living Composites with Ordered Microstructures and Exceptional Mechanical Properties. Issue 13 (19th February 2021) - Xin, An; Su, Yipin; Feng, Shengwei; Yan, Minliang; Yu, Kunhao; Feng, Zhangzhengrong; Hoon Lee, Kyung; Sun, Lizhi; Wang, Qiming
Abstract: Living creatures are continuous sources of inspiration for designing synthetic materials. However, living creatures are typically different from synthetic materials because the former consist of living cells to support their growth and regeneration. Although natural systems can grow materials with sophisticated microstructures, how to harness living cells to grow materials with predesigned microstructures in engineering systems remains largely elusive. Here, an attempt to exploit living bacteria and 3D‐printed materials to grow bionic mineralized composites with ordered microstructures is reported. The bionic composites exhibit outstanding specific strength and fracture toughness, which are comparable to natural composites, and exceptional energy absorption capability superior to both natural and artificial counterparts. This report opens the door for 3D‐architectured hybrid synthetic–living materials with living ordered microstructures and exceptional properties. Abstract : A paradigm is presented to guide living bacteria to grow bionic mineralized composites. The strategy demonstrates a class of living composites with ordered microstructures and exceptional mechanical properties. This research progress highlights an exciting opportunity for future bionic composite materials by tailoring the interaction or communication between living organisms and 3D‐printed synthetic materials.